Efek Penambahan APK Pipa Kapiler Bersirip Sebagai Penghantar Panas Terhadap Performance AC Pada Aplikasi ACWH - Chandra Amirsyah Siregar; Ahmad Marabdi Siregar; Dana Setiawan (Rekayasa Material, Manufaktur dan Energi, 2021)
Technological advances encourage researchers to continue engineering technology. One of them is to increase the function of the Air Conditioner (AC) from air conditioning to air conditioning and the provision of hot water for bathing needs (Air Conditioner Water Heater / ACWH). This study aims to analyze the performance of the air conditioner due to the addition of a water heater application. The water capacity in the tank is 60 liters using a capillary tube heat exchanger with the addition of fins. The test was carried out at 3 different evaporator temperatures, namely 16 0C, 18 0C and 20 0C. Data were collected for 60 minutes. The result is that the ACWH application is able to provide hot water for bathing needs, with a temperature of 55.5 0C at the evaporator temperature test of 18 0C. However, the addition of this application resulted in a decrease in AC performance (COP). The COP AC value obtained in the 20 0C test was 3.071 while the ACWH application was 2.081.